Temporal and spatial variability of zoobenthos recruitment in a north-east Atlantic marine reserve. (November 2014) - Ronowicz, Marta; Kukliński, Piotr; Lock, Kate; Newman, Philip B.; Burton, Mark; Jones, Jennifer
<x content-type="archive" xml:space="preserve">Abstract</x> Submerged artificial surface imitates newly available habitat for settlement of marine fauna. It also enables study of the timing of benthic larval settlement. Such knowledge is important if the model of possible recovery after disturbance in protected areas is to be assessed. During this study recruitment of sessile benthic invertebrate fauna at spatial and temporal scales was investigated using artificial panels submerged in the Skomer Marine Nature Reserve (Wales, UK). Panels were exchanged monthly between May 2009 and September 2011 (with the exclusion of winter time). Recruitment was highly variable with regard to time and distribution; abundance and number of recruiting species varied significantly between sites (about 2 km apart from each other), depths (6 and 12 m), position on panels (top or underside) and years without any obvious trends. The highest number of individuals and highest values of species richness were at Bernies Rocks, at the greater depth and on the underside surface of panels. Bryozoans were the dominant taxon on panels in each studied year and month. Most macrofaunal species noted on panels exhibit a colonial life strategy with short-lived, non-feeding larval stage. Although many species settle all year round, levels of settlement usually peak in summer months, showing a seasonal recruitment pattern (Bugula fulva, Spirobranchus triqueter, Chorizopora brongniarti and Escharoides coccinea). Some species had a pronounced settlement peak in spring (e.g. Electra pilosa and Balanus crenatus).